PAEDIATRIC CASE OF 3-METHYLCROTONYLGLYCINURIA WITH ENCEPHALOPATHY: A CASE REPORT FROM PAKISTAN - Ali Gova, Murtaza; Noor, Noshaba; Nawaz, Hira; Rameen Akhter Molani, (Journal of Ayub Medical College Abbottabad, 2024)
3-Methylcrotonylglycinuria is a common inborn error of metabolism (IEM) resulting from the deficiency of 3-Methylcrotonyl-CoA carboxylase (3-MCC) and its prevalence ranges from 1:2400 to 1:6800. The disease may be asymptomatic or may present with signs of "metabolic crisis". In our four and a half months old male patient, the disease manifested as fever, fits and an altered level of consciousness, along with signs and symptoms of metabolic crisis. The purpose of this case report is to highlight a clinical presentation of 3-MCG, as seen in this patient to ensure timely diagnosis and treatment.